Anti-Hypochlorite, Antioxidant, and Catalytic Activity of Three Polyphenol-Rich Super-Foods Investigated with the Use of Coumarin-Based Sensors - Karolina Starzak; Tomasz Świergosz; Arkadiusz Matwijczuk; Bernadette Creaven; Janusz Podleśny; Dariusz Karcz (Biomolecules, 2020)
The anti-hypochlorite activity of açaí (Euterpe oleracea Mart.), goji (Lycium barbarum L.) and schisandra (Schisandra chinensis) fruit extracts were assessed by determining the reactive chlorine species (RCS)-scavenging ability of these three “super-food” berries. In addition, the aqueous extracts obtained were employed as both the media and the catalyst in a green chemistry approach to the synthesis of a coumarin-based fluorescence turn-off sensor, which was then used for anti-hypochlorite activity testing. The aqueous extracts were also assessed for total phenolic content (TPC), using the Folin–Ciocalteu method, and the antioxidant activity using the ABTS+• assay. Moreover, the main water-soluble polyphenolic constituents of the extracts were identified by the HPLC-PDA-ESI-MS technique. Among the extracts tested, açaí demonstrated the highest anti-hypochlorite and antioxidant activities, while the highest TPC value was found for the goji extract. All extracts demonstrated modest catalytic activity as Knoevenagel condensation catalysts.